The Effect of Irradiation Methods on Biomass Yield on Mix of Corn (zea mays) and Mung Bean (Vigna radiata) with Hydroponic system - Iin Susilawati; Lizah Khairani (Jurnal Nutrisi Ternak Tropis dan Ilmu Pakan, 2023)
The objectives of this research was to find effect of irradiation methods on the production of biomass fresh weight, leaf and root dry weight on  combination of mung bean and corn with hydroponic system. This research was design with experimental method using Completely Randomized Design   with 2 treatmens and 9 replications. The observed of P1 = irradiation method with the sunlight for  12 hours and P2 = irradiation method with  LED grow light 7. watt for  16 hours. Parameters observed were biomass fresh weight,  leaf and root dry weight Data were analyzed using of two samples Independent T-tes. The result showed that biomass fresh weight and leaf dry weight of irradiation with  LED  higher   than  irradiation  with the sunlight,  the average’s 3155,844 g/m2, and 55,14 g/m2, but no significant effect on dry weight of root.